Conversion of motorcycle fueling system from carbureted to Electronic Fuel Injection (EFI) - Adnan Katijan, 1974-, author 613186; Mohd. Farid Muhamad Said, supervisor 186811; Fakulti Kejuruteraan Mekanikal 8081 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Sarjana Sains (Kejuruteraan Automotif))